The Role of the Principal in Improving the Professionalism of Teacher Discipline in Teaching (Case Study at MI Al-Azizy Daleman Karduluk) - Faizun Najah; Robitul Abror (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes the principal's strategy in improving teacher discipline at MI Al-Azizy Daleman Karduluk, a private madrasah with limited facilities. Using a qualitative case study approach, data were collected through interviews, observations, and documentation of the principal and teachers. The results of the study revealed four effective strategies: (1) spiritual motivation based on religious values ​​("teaching as worship") which builds teachers' intrinsic commitment; (2) concrete role models of the principal through consistent time discipline; (3) empowerment of teachers with additional tasks to create a sense of belonging; and (4) supervision of learning administration as a control mechanism. The main supporting factors include family ties between teachers as alumni of the foundation and consistent role models of leaders, while limited teacher welfare and variations in individual awareness are significant challenges. These findings strengthen the theory of transformational leadership and social learning in the context of Islamic education, showing that non-material approaches (spiritual, relational, and role models) are able to overcome limited material resources. This study provides practical contributions for private madrasah managers in developing a model of teacher discipline coaching that is adaptive to local conditions.